Pré-condicionamento nutracêutico com misturas de óleos ômega 3, 6 e 9 na artrite aguda induzida por zymosan em ratos - Cavalcante, Beatriz Torres de Melo (2014)
Artritis is an inflammatory condition that affects synovial articulations. The most relevant manifestations are decreased pain threshold and edema. A possible alternative as adjuvant therapy to this disease is the inclusion of nutraceutics in the diet. In the present study preconditioning with mixes of oils omega 3, 6 and 9 was used at an experimental model of acute artritis induced by zymosan (Zy) in rats. The objective of this study was to evaluate the antiinflammatory and antinociceptive effects of these mixes which contain high omega- 9:omega-6 ratio (3.4:1) and low omega-6:omega-3 ratio (1.4:1). These oil mixes contained different sources of omega-3: Mix 1 with alfa-linolenic acid, Mix 2 with alfa-linolenic, eicosapentanoic and docosaexanoic acids, and Mix 3 with alfa-linolenic and docosaexanoic acids. The monoinsaturated omega-9 fatty acids present antioxidant action whereas the poliinsaturated fatty acids omega-3 present antiinflammatory effects and the omega-6 fatty acids are proinflammatory. Thirty male wistar rats weighing 180-200g were used, for each experimental group. The animals were randomly distributed in two groups: Control (=12) and Test (n=18). The Control group was subdivided into groups: Negative Control whose animals received water orogastrically during 7 days (n=6), and Positive Controls whose animals received no oil mixes during 7 days but were treated with either dexametazone (DEXA – n=6) at the experiment day (day 8). The Test group was distributed into three groups of 6 rats subjected to orgastric administration of mixes 1, 2 and 3. On day 8 all animals had artritis induction by intraarticular injection of zymosan (1mg/50microlitters) in the right knee. Analised variables were articular incapacitation (A.I.), leucocyte migration, mieloperoxidase (MPO) activity, articular edema, vascular permeability, articular capsule immunostain for iNOS and NF-kB and histopathological analysis. Hypernociception was induced by carrageenan and PGE2. Results demonstrated a significant decrease (p<0.05) in A.I. during the third hour in animals preconditioned with mixes 1, 2 and 3, to level similar to that of those treated with DEXA. As concerned to leucocyte migration, there was a significant reduction (p<0.05) in the number of leucocytes in the aticular wash in rats preconditioned with all three mixes, as well as decreased activity of MPO (p<0.05) similar to what was found in animals treated with DEXA. Edema was inhibited and vascular permeability diminished in all groups preconditioned with all mixes (p<0.05). In animals of Mix 3 the decrease in vascular permeability was even more pronounced as compared to all other groups (p<0.001). Histopathology analysis showed a decrease in cellular inflitration and prevention from loss of articular capsule integrity in rats preconditioned with mixes 1 and 2. Immunohistochemical stain for iNOS and NFkB was significantly smaller in rats of groups 1, 2 and 3, similar to that of DEXA group. All oil mixes showed a significant inhibitory effect (p<0.05) as concerned to antinociception through the use of a model of plantar mecanic hiperalgia induced by carrageenan, similar to that of rats of INDO group, a drug used in the positive control . On the other hand, the same did not occur when hiperalgia was induced by PGE2. The results therefore suggest that preconditioning with mixes 1, 2 and 3 present antiinflammatory and antinociceptive effects, as well as decreases synovial expression of iNOS and NFkB. However, the observed antinociceptive effect appears to be indirect and due to the antiinflammatory effect.